Tinjauan Penelitian Terkini tentang Pemanfaatan Komposit Serat Alam untuk Komponen Otomotif Review on Current Research on Utilization of Natural Fiber Composites for Automotive Components - Subyakto Subyakto; Mohamad Gopar (Masyarakat Peneliti Kayu Indonesia, 2009)
Automotive industries now are targeting their components to become “green composites” which are environmentally friendly, renewable, biodegradable, recyclable, light, and strong. Natural fibers have potential to use as substitute for material composites traditionally used by automotive industries such as fiber glass, carbon fiber and aramid that are non renewable, non degradable and non recyclable. Therefore the use of synthetic fibers should be reduced. European End of Live program required that in 2015 all new cars should be recyclable. Composites reinforced with natural fibers will play important role as automotive materials. Some advantages of natural fibers compare to synthetic fibers are renewable, biodegradable, recyclable, non toxic to human and environment, low density, better specific mechanical properties, non abrasive to tools, and lower cost. Utilization of natural fibers can reduced car weight up to 30%, and energy to produce natural fibers is lower compare to glass fibers.Natural fiber resource, their characteristics and current research on their utilization for automotive components were reviewed. Hopefully it will stimulate and raise the research on utilization of natural fibers in Indonesia, especially for high value products such as automotive components